Similarity Detection in Android Screen: a comparative analysis using Information Retrieval, Embeddings and Vision Language Models - Souza, Daniel Augusto R. Lima de; Ramos, Fabio C.; Oliveira, Cainã S. de; Veras, Edluce L.; Lopes, Paulo Fabricio da F.; Santos, Barbara L.; Souza, Jose Diogo B. de; Oliveira, Adriano De O. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the Web, 2025)
The growing mobile application development market brings an urgent need for tools capable of evaluating and comparing similarities between screens of different applications. This article proposes a comparative analysis of methods for similarity detection on Android screens, integrating Information Retrieval (IR), embedding models (BGE-M3, Snowflake-Arctic-Embed2, Nomic-Embed-Text) and Vision Language Models (VLM) such as qwen2.5vl:7b and gemma-3:27b. The study addresses challenges like design redundancies and UI test inconsistencies by using combined pipelines: IR, embeddings, and VLM for screen identification. The results demonstrate the strengths and limitations of each approach, providing insights into their applicability in mobile UI similarity detection.